Green synthesis using cherry and orange juice and characterization of TbFeO3 ceramic nanostructures and their application as photocatalysts under UV light for removal of organic dyes in water. (10th April 2020) - Mehdizadeh, Pourya; Orooji, Yasin; Amiri, Omid; Salavati-Niasari, Masoud; Moayedi, Hossein
Abstract: Water pollution becomes a serious global concern threatening the entire biosphere and affecting the lives of many millions of people around the world. Water pollution causes a variety of diseases and millions of people die annually because of illness related to the dirty water. TbFeO3 nanostructures were synthesized by green sonication method. Cherry and orange juice were used as natural surfactant and results were compared by those obtained by chemical surfactants (SDS and CTAB). Then as-prepared TbFeO3 nanostructures were applied to treat wastewater containing Methyl orange, Acid Blue 92, Acid Black 1, and Acid Brown 214. In addition, the effect of pH and containment concentration on the photocatalytic activity of TbFeO3 nanostructure was studied. Using orange juice as surfactant leads helped to boost the photocatalytic activity of TbFeO3 nanostructure. As prepared TbFeO3 nanostructure were characterized with XRD, SEM, TEM, EDX, DRS, BET and FT-IR. Graphical abstract: Image 1076 Highlights: TbFeO3 nanostructures were prepared by a green and simple sonochemistry method. Using orange juice in synthesis of TbFeO3 nanostructures leads to produce a very pure. As-prepared TbFeO3 nanostructures were used to remove dyes in water. We studied the effect of the concentration of contaminant and pH on the degradation efficiency.